Respuesta :
Answer:
x = ±√-1 or x = ±√-5
Step-by-step explanation:
It is given an equation x^4 + 6x^2 + 5 = 0 -----(1)
Solve equation using substitution
Let y = x^2
eq (1) ⇒ y^2 + 6y + 5 =0
Solve y^2 + 6y + 5 =0
y^2 + 6y + 5 = y^2 + 1y + 5y + 5
= y(y + 1) + 5(y + 1)
= (y + 1)(y + 5)
Therefore the zeros are -1 and -5
x^2 = -1 or x^2 = -5
x = ±√-1 or x = ±√-5
Answer:
x = ±√5i or x = ±i is solution of given equation.
Step-by-step explanation:
We have given an equation.
x⁴+6x²+5 = 0
We to solve it using substitution.
Let u = x²
then, u² = x⁴
Putting above value in given equation , we have
u²+6u+5 = 0
Now, use method of factorization.
split the middle term of above equation
u²+5u+u+5 = 0
u(u+5)+1(u+5) = 0
(u+5)(u+1) = 0
Applying zero product property , we have
u+5 = 0 or u+1 = 0
u = -5 or u = -1
Putting u = x² in above equation, we have
x² = -5 or x² = -1
Taking square root of both sides of equations, we have
x = ±√-5 or x = ±√-1
x = ±√5i or x = ±i where i = √-1.